Pengaruh Penerapan Model PBL Berbantuan Video Animasi Terhadap Hasil Belajar Tema 8 Subtema 3 - Dewi Astuti; Yuli Mulyawati; Santa Santa (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine the effect of the PBL model on learning outcomes in Theme 8 Sub-theme 3 at SD Negeri Sukamantri 01 Bogor Regency Class IV, especially in Thematic learning. This type of research is a type of quantitative research with a quasi-experimental approach and nonequivalent control group design. The population in this study were all fourth grade students at SD Negeri Sukamantri 01 for the academic year 2021/2022 totaling 58 students who were also the research sample. Based on data analysis, there is a difference between the average pretest and posttest learning outcomes. Based on the calculation of tcount (4.47738) > ttable (2.00488) then Ho is rejected. In addition, the average value of N-Gain in the experimental class group was 79 while in the control class it was 60. It can be stated that the PBL model has an influence on learning outcomes Theme 8 Sub-theme 3 class IV at SDN Sukamantri 01 Bogor Regency.